2023
DOI: 10.1002/aenm.202300684
|View full text |Cite
|
Sign up to set email alerts
|

Transformed Solvation Structure of Noncoordinating Flame‐Retardant Assisted Propylene Carbonate Enabling High Voltage Li‐Ion Batteries with High Safety and Long Cyclability

Abstract: The evolution of high‐energy‐density lithium‐ion batteries (LIBs) urgently requires the development of high‐safety electrolytes with high voltage resistance. Here, noncoordinating flame retardant pentafluoro‐(phenoxy)‐cyclotriphosphazene (FPPN) endows propylene carbonate (PC, 70 vol%)‐based electrolytes with high graphite anode compatibility, non‐flammability, high voltage stability, and excellent separator/electrode wettability. Theoretical calculations reveal that FPPN significantly affects Li+‐PC‐anion inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Generally, the lower surface tension of electrolyte means better wettability. 30 It is found that with the increase of the amount of HFPN, the interfacial impedance of the Li–Li cells gradually increases (Fig. S3†), and the wettability of the electrolyte on separator gradually deteriorates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the lower surface tension of electrolyte means better wettability. 30 It is found that with the increase of the amount of HFPN, the interfacial impedance of the Li–Li cells gradually increases (Fig. S3†), and the wettability of the electrolyte on separator gradually deteriorates (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Self-heating rate of charged LiCoO 2 /graphite pouch cells with the temperature distribution during the nail penetration test. Reproduced from ref . Copyright 2023 Wiley-VCH.…”
Section: Applications Of Tdesmentioning
confidence: 99%
“…For example, lithiophobic pentafluoro(phenoxy)cyclotriphosphazene (FPPN) is directly used in PC electrolytes because it facilitates Li + desolvation and delays the thermal runaway temperature by passivating electrodes (Figure 7b). 48 Third, the crosstalk between carbonates and flame retardants is relieved by encapsulating the flame retardant in lithiophobic cosolvents. 9,10-Dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) interacts with carbonates by forming P−H bonds in common electrolytes, leading to interphase degradation.…”
Section: Intrinsic Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Lithium-ion batteries have been widely used in 3C electronic products, energy storage devices, and power batteries due to their high operating voltage, environmental friendliness, and long cycle life. The conventional liquid electrolyte used in Li-ion batteries makes it difficult to match high-voltage cathodes such as Li-rich Mn-based layered oxides due to its narrow electrochemical window, resulting in limited energy density. Moreover, flammable liquid electrolytes pose potential safety problems for Li batteries. Given these concerns, significant effort has been devoted to exploring solid-state electrolytes (SSEs) with wider voltage windows and high safety, including perovskite , antiperovskite type, sulfide type, Na super ionic conductor (NASICON) type and garnet type electrolytes. Among these, garnet-type electrolytes have attracted much attention due to their excellent stability toward Li metal and air and fast ionic conduction. , However, the poor wettability and large interface resistance of garnet electrolytes and Li metal anode seriously obstruct the electrochemical performance of Li-ion batteries. , …”
Section: Introductionmentioning
confidence: 99%